GAMBARAN WORK-FAMILY CONFLICT PADA IBU SINGLE PARENT - Angel Gracia Florin Loupatty; Ratriana Yuliastuti Endang Kusumiati (Jurnal Cakrawala Ilmiah, 2024)
This study aims to determine the description of work-family conflict in single parent mothers both caused by divorce and death. The subjects in this study were three single parent mothers who work and have children aged 2-6 years. The discovery of subjects was carried out using the quota sampling method which is a non-probability sampling technique where participants are selected based on predetermined characteristics. The data analysis technique used is thematic data analysis which aims to identify patterns or find themes through the data that has been collected by researchers. In achieving valid results in this study, the researcher conducted a member check which aims to find out how far the data obtained with what is given by the data giver so that it will be more credible or trusted. In this study, researchers found that the three subjects had the same demands when becoming single parent mothers. Moreover, having children who are in pre-school age where this age is a very important age for child growth, but the three subjects try to meet the needs of their children in various ways. Each subject also experienced more than one type of conflict, namely subject J experienced time-based conflict and behavior-based conflict, subject T experienced time-based conflict and strain-based conflict, and subject U experienced strain-based conflict and behavior-based conflict.